Designing and Developing Leak Detection Tool Prototype for Liquefied Petroleum Gas Cylinders - Hambali, Ahmad; Tambun, Madschen Sia Mei Ol Siska Selvija; Kurniawan, Muhammad Ari; Triyanto, Irfan Rusydi; Ikhsan, M. Rizki (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2024)
Frequent fire incidents from three kilograms Liquefied Petroleum Gas (LPG) cylinder leaks have raised concerns and criticism of the government’s gas conversion program, highlighting the need to prevent leaks caused by excessive pressure or damaged components. This study aims to design and develop a prototype tool to detect leaks in 3 kg LPG cylinders, enhancing operational safety and efficiency. The research employed an observational approach, involving direct field observations at PT Agra Budi Gas Utama SPBE. The study examined the operational processes, the application of LPG leak detection tools, and the interaction between operators and existing equipment. The research reveals that Nordic Body Map (NBM) analysis identifies moderate injury risks, with workers experiencing pain in the shoulders, hands, back, and legs due to repetitive movements, prolonged standing, and non-ergonomic workstations. Using anthropometric data of the Indonesian population (50th–95th percentiles), the design introduced key features such as a height-adjustable hydraulic jack, a conveyor system to reduce manual labor, a 60.75-liter water container for leak detection, and safety locks for improved stability. These innovations aim to minimize musculoskeletal injuries, optimize posture, and enhance productivity, with ongoing evaluation recommended for sustained workplace safety and efficiency. Indeed, the trial implementation of the prototype demonstrated its effectiveness in facilitating the detection of leaks, significantly improving the efficiency and accuracy of leak checks performed by operators.